1405 Significant Weight Loss in Breastfed Infants in the Early Postnatal Life. (October 2012) - Mitra, A; Parish, E; Sohn, AY; Chetan, R
Abstract : Background and Aims: Breastfed newborn infants can develop significant weight loss in early postnatal period associated with hypernatremia. In our hospital, breastfeeding support is provided to mothers both in hospital and community. This breastfeeding care pathway is based on the UNICEF breastfeeding policy. In spite of this sontinuous effort, several newborn infants with significant weight loss need hospital re-admission in the early postnatal period. Methods: A retrospective audit was performed over 6 months (Jan 2011– June 2011) period. Management of all breastfed infants admitted with weight loss (>7% of birth weight) with or without other clinical symptoms of dehydration were reviewed. Information was collected from infant clinical notes, discharge summaries, hospital pathology reporting system and maternal notes. Results: 1908 infants were born during this period, 33 infants (1.73%) required readmissions. No risk factor was identified in 3 infants, 30 infants had one or more risk factors, commonest being caesarean section delivery (61%) followed by infants born to 'first time mother's (33%). 72% of the infants developed jaundice. Majority of the infants(59%) were managed with breast feeding support only whereas 15% needed intravenous fluid support. Most infants (69.6%) were discharged within 48 hrs of admission. Half of the infants developing hypernatremia had comparatively mild weight loss (≤10% of birth weight). Conclusions: Weight loss and Hypernatremia continues to be a problem in neonates particularly in 'at risk' infants. Most of these infants responded well to enteral feeding only. Degree of hypernatremia was not always proportion to the degree of weight loss.